2022
DOI: 10.1002/adfm.202209157
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Cyanobacteria can Clearly Induce Efficient Muscle Tissue Regeneration of Bioprinted Cell‐Constructs

Abstract: Tissue engineering strategies using cell‐laden constructs have shown promising results in the treatment of various types of damaged tissues. However, inadequate oxygen delivery to the macroscale 3D cell‐constructs for regenerating skeletal muscle tissue has remained a multiplex issue owing to the pivotal factors including cell metabolism and several regulatory intercellular pathways that eventually influence various cellular activities and determines cell phenotype. To overcome this issue, a photosynthetic cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…S. elongatus has facilitated oxygenation in cardiac tissues during episodes of ischemic stroke 76 . The application of S. elongatus has been extended to the domain of bioprinting, providing oxygenation for cell constructs under hypoxic conditions 77 .…”
Section: Biological Molecules As Oxygen-controlling Strategiesmentioning
confidence: 99%
“…S. elongatus has facilitated oxygenation in cardiac tissues during episodes of ischemic stroke 76 . The application of S. elongatus has been extended to the domain of bioprinting, providing oxygenation for cell constructs under hypoxic conditions 77 .…”
Section: Biological Molecules As Oxygen-controlling Strategiesmentioning
confidence: 99%
“…The work showed an external electric field activates the cell membrane potential and voltage-gated ion channels to promote cell alignment and proliferation. 37 This observation suggests that a potential exists for the electric-field coupling synthesis of biohybrid systems with adhering high-dense cells.…”
Section: Introductionmentioning
confidence: 99%
“…An exciting concept is to exploit photosynthetic oxygen production by microalgae or cyanobacteria for delivery to the oxygen-consuming cells 18 21 . Therefore, cocultures of mammalian cells with photosynthetically active cells are established and investigated; first studies demonstrated both, their great potential and their limitations 22 26 . A crucial aspect of the development of a cultivation regime compatible with both cell types is the illumination, which is essential to enable photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above-mentioned applications, which use light at a very specific wavelength and relatively short incubation times, such a coculture approach rather requires a long-term, continuous light exposure to ensure a continuous oxygen supply. In addition, photosynthetically active microorganisms are adapted to sun light with its broad spectrum and therefore, warm white light is the first choice for this approach 18 , 19 , 22 , 23 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%